Analisis Implementasi Manajemen Sumberdaya Manusia dan Fungsi Pengendalian Manajemen Pada Ummu Abdullah Catering dan Aqiqah di Surabaya - Novie Noordiana Rachma Yulia; Wahyu Rochana; Agung Pribadhi (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The object of this writing is a family business actor in the culinary sector who still manages his business using conventional methods. Before the pandemic, sales were made in large portions for parties, so when the Covid 19 pandemic emerged, accompanied by recommendations for physical distancing, sales experienced a significant decline, thus requiring business owners to do several things to survive and develop. . From the research results it can be concluded that: 1. Human resource management process activities have been applied but are still in a simple, non-formal and unrecorded context. These activities include employee identification and selection, orientation for new employees, and training for new and existing employees. Strategies to retain employees who are competent and have high productivity have also been implemented. There is no health insurance for employees in the object of analysis, there is only a small financial assistance for medical treatment and giving vitamins to employees as a form of prevention so they don't fall sick. Regarding the issue of balance between work and personal life, the owner gives employees the freedom to bring their children to work if conditions do not allow the children to be left at home. 2. The control function has also been applied to the object of analysis, although it is still simple, informal and not recorded. Financial control through calculating ratios has not been applied because the object of analysis has never made written and formal financial reports such as Profit and Loss reports and Balance Sheets. Balance Score Card and Benchmarking have also not been applied by the object of analysis. Control devices in the form of Feedforward, Concurrent and feedback control have been applied by the object of analysis but still in a simple, informal and unwritten manner.